THE PRINCIPLE OF ASYMMETRY IN THE ADMINISTRATIVE LEGAL RELATIONS - Balayan, Norayr (State and Law, 2020)
The principle of legal asymmetry in the theory of law is the principle of the principle. This principle was first recorded in the Constitution of the RA in 2015. The means chosen for restriction must be commensurate to the significance of the basic right or freedom being restricted. This principle is widely used in administrative-legal relations, since it was first recorded by the legislative act in this area as an independent principle. The principle of asymmetry is usually not applied by administrative bodies, in turn, it contributes to unlawful restriction of human rights and freedoms. If the administrative bodies follow this constitutional principle, this will help to establish and to strengthen the rule of law.